P0089KEAP1/NRF2 PATHWAY REGULATES GFR BY INCREASING THE GLOMERULAR EFFECTIVE AREA WITHOUT AFFECTING THE AFFERENT/EFFERENT ARTERIOLE RATIO. (6th June 2020) - KIDOKORO, KENGO; Wada, Yoshihisa; Kondo, Megumi; Tokuyama, Atsuyuki; Itano, Seiji; Sasaki, Tamaki; Wigley, Chris; Proksch, Joel; Meyer, Colin; Kashihara, Naoki
Abstract: Background and Aims: The Keap1/Nrf2 pathway regulates the expression of a series of cytoprotective, anti-inflammatory and antioxidant genes. The Nrf2 activator, bardoxolone methyl (BARD), has consistently increased estimated GFR (eGFR) in clinical studies in patients with chronic kidney disease. BARD demonstrated improvement of renal function assessed by inulin clearance, the clinical gold standard for measuring GFR, in diabetic kidney disease patients. These findings suggest the Keap1/Nrf2 system is deeply involved in the regulatory mechanisms of GFR. However, the precise mechanisms are not fully elucidated. We pharmacologically and genetically investigated the mechanisms of GFR regulation by Keap1/Nrf2 system using in vivo multiphoton microscope (MPM) imaging techniques. Method: C57BL/6 (Cont), Nrf2 knockout (Nrf2-KO), and Nrf2-activated Keap1-knockdown mice (Keap1-KD) were used. The mice were treated the synthetic triterpenoid RTA dh404 (10 mg/kg/day by gavage) which is a Nrf2 activator for rodents, for a week. We successfully developed the technique to evaluate single-nephron GFR (SNGFR) using MPM (Circulation 2019). The glomerular hemodynamics, diameter of the afferent/efferent arterioles and glomerular permeability were also evaluated. The calcium influx into cells in response to ATP and angiotensin II stimulation and the effect on [Ca2+]i by RTAdh404 were evaluated using Fluo 4 and Fura red in cultured mesangial cells and podocytes. Production of reactive oxygen species and nitric oxide (NO) availability were assessed by fluorescent method using CellROX® Deep Red and diaminofluorescein-FM diacetate (DAF-FM DA) upon the exposure to these stimuli. Results: SNGFR in Keap1-KD mice was significantly higher than in the control (9.13±0.55 vs 4.40±0.39 nl/min, Figure 1). RTA dh404 increased SNGFR in the control but not in the Nrf2-KO mice (6.00±0.40 vs 4.66±0.35 nl/min, Figure 1). There was no significant change in the ratio of the glomerular afferent/efferent arteriole diameter in all groups. RTA dh404 treatment increased glomerular volume but did not affect the glomerular permeability of albumin and 40kd-dextran. RTA dh404-treatment inhibited calcium influx into cultured podocytes and mesangial cells induced by angiotensin II or ATP, thereby affecting contractile responses. Oxidative stress and NO-bioavailablity were also ameliorated with RTA dh404. Conclusion: The Keap1/Nrf2 pathway plays a pivotal role in controlling GFR and presumably underlies the effect of BARD on GFR in patients.